The role of tennis coaches in regulating their players' emotional states : an exploratory study - Müller, Stephanie (2014)
During the past few decades, the ability to perceive, understand, and regulate emotions efficiently has received widespread attention in sport settings (Hanin, 2000; 2004; Robazza, Pellizzari, & Hanin, 2004). Moreover, this line of research has mainly focused on the intrapersonal aspect of emotions. The aim of the present study was to examine the role of tennis coaches in regulating their players’ emotional states. The present study explored (a) tennis players’ emotional states related to their best and worst performances, (b) coaches’ accuracy in assessing players’ emotional experiences within these performances, and (c) self- and interpersonal emotional regulation strategies of tennis coaches and players.